Perangkap dalam Pembuatan Keputusan - Kenny Dewi K.H (Center for Economic Studies Universitas Katolik Parahyangan, 1999)
Decision making is defined as the selection of a course of action from among alternatives; it is the core of planning. A plan cannot be said to exist unless a decision — a commitment of resources, direction, or reputation — has been made. Think back on the past decision has been made that caused considerable pain for the decision maker, it could be concluded that some of the biggest regrets come from faulty decision making. Sometimes the decision making process is relied on, so-called,